Determinants of Intention to Use QRIS as a Transaction Tool for Mobile Banking Users of Islamic Banking - Indarningsih, Nur Aisyah; Setyono, Joko (IQTISHADIA, 2024)
This study aims to analyze the determinants of intention to use the Quick Response Code Indonesian Standard (QRIS) on mobile banking users of Islamic banking by integrating the religiosity variable as a moderator in the Unified Theory of Acceptance and Use of Technology 3 (UTAUT3) model to predict user intentions and behavior. UTAUT3 consists of performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habits, and personal innovativeness as determinants of intention and behavior using QRIS mobile banking. A total of 255 respondents were selected as samples using the purposive sampling method. This study uses a quantitative approach with SEM-PLS (Structural Equation Modeling - Partial Least Squares) analysis using SmartPLS software version 3.0. Empirical results show that social influence, facilitating conditions, price value, habits, and personal innovativeness significantly positively affect behavioral intention to use QRIS mobile banking in Islamic banking. Conversely, performance expectancy, effort expectancy, and hedonic motivation do not have a significant effect on this intention. In addition, behavioral intention, habits, and personal innovativeness are proven to have a significant positive influence on the actual behavior of using QRIS mobile banking in Islamic banking. However, facilitating conditions do not have a significant effect on usage behavior. Religiosity as a moderating variable is unable to moderate the relationship between behavioral intention and actual behavior of using QRIS. The implications of this study are to provide insight for the Islamic banking industry to develop marketing strategies based on social values and personal innovativeness and to facilitate users with conditions that support QRIS adoption. This study also contributes to developing consumer behavior theory through a more comprehensive integration of UTAUT3 in the context of Islamic banking.